Courbe de mortalité de la bactérie Proteus mirabilis par irradiation UV - BAKRETI DIT BENALLOU, Abdelkrim (My University, 2025)
A mutation is defined as an unexpected change that occurs in the hereditary traits of living organisms. It is a rare phenomenon, often associated with a dysfunction in natural mechanisms, but it remains important in the study of genetic diversity and the changes affecting bacteria. In this work, ultraviolet rays were used as a physical mutagenic agent to induce mutations in Proteus mirabilis. The results showed that prolonged exposure to these rays leads to a gradual weakening of bacterial activity and an increase in its sensitivity, eventually resulting in cell death. Antibiotic sensitivity tests, carried out before and after exposure to the rays, indicated that the studied strains remained sensitive to these antibiotics and did not show any new resistance. These results confirm the inhibitory and lethal effect of ultraviolet rays on Proteus mirabilis, thus highlighting their importance as an experimental tool in the study of mutations and bacterial viability.
Keywords: mutations, ultraviolet rays, Proteus mirabilis, antibiotics